THE EFFORTS TO IMPROVE CREATIVITY LEARNING MATHEMATICS BY USING METHOD OF GUIDED DISCOVERY IN SEVENTH GRADE STUDENTS OF SMP NEGERI 3 SENTOLO KULON PROGO - Dwi Novita Sari; Edi Prajitno (Universitas Ahmad Dahlan, 2017)
In research aims to understand an increase in creativity learn math to their students class vii the first half odd SMP Negeri 3 Sentolo in the academic year of 2016 / 2017. This research uses a method of guided discovery. The subject at this research is a student VII B SMP Negeri 3 Sentolo Kabupaten Kulon Progo in the academic year of 2016 / 2017 which consisted of 16 students' son and 14 students' daughter. Technique data collection it will be a method of observation, interview, documentation, and tests the discussion. Obtained the average the percentage creativity to study for students from the results of sheets of observation in cycle I of 29,79 % in the less. Cycle II increased by 61.71% in both categories and the average percentage of classical and exhaustiveness of test results of 46.667%. Cycle III increased by 79.21% in both categories and the average percentage of classical and exhaustiveness of test results of 80.000%. According to the interviews students and teachers showed a positive response from students and teachers.